Citra Psikis Perempuan Madura dalam Novel Damar Kambang karya Muna Masyari (Kajian Tipologi Kepribadian Eduard Spranger): Psychic Image of Madurese Women in the Novel Damar Kambang by Muna Masyari (Study of Eduard Spranger's Personality Typology) - Wahyudin, Sapta Arif Nur; Sutejo, Sutejo (Kibas Cenderawasih, 2024)
This research aims to describe the psychological image of Madurese women in the novel Damar Kambang by Muna Masyari. The theory used in this research is Eduard Spranger's personality typology. The format chosen is a qualitative descriptive format. Data was collected using note-taking techniques. Namely, researchers read the work carefully, then record the data containing the psychological image of women. From the results of the analysis, it is known that there are 4 female characters with the following description of their psychological image. (1) Marintem is portrayed as a restless and patient woman. However, after a major conflict occurred, she became an arrogant, greedy and jealous woman. As for the psychic image, Marintem is classified as an aesthetic and powerful person. (2) Cebbhing is portrayed as an innocent and obedient woman. However, after a big problem happened to her, she became a brave, unyielding and rebellious woman. As for his psychological image, Cebbhing is classified as an intellectual, aesthetic, religious and social person. (3) Mrs. Cebbhing is portrayed as a woman who is reverent towards her husband. As for her psychological image, Mrs. Cebbhing is classified as an economic and religious person. (4) Mrs. Kacong is portrayed as an obedient woman, reverent towards her husband, and restless. As for her psychological image, Mrs. Kacong is classified as an aesthetic and religious person.